Penerapan Brief Strategic Family Therapy (BSFT) untuk Meningkatkan Komunikasi Orang Tua-Anak - Moya A. D. Martiningtyas; Ira Paramastri (Faculty of Psychology, Universitas Gadjah Mada, 2015)
Brief Strategic Family Therapy (BSFT) is a family therapy that usually use for children with problem behavior. Purpose of BSFT is helping the family to change the maladaptive pattern, such as: lack of communication between parents and children so the behaviors problem can be decreased and dissapear. BSFT is implemented to a family with children that showing symptoms of Oppositional Defiant Disorder (ODD). BSFT was performed in 2 month and able to change maladaptive pattern of communication in the family so the children’s behavior problem decreased. Follow up after 8 month shows that there were less fighting in the family and improvement of communication between parents and their children.